2019
DOI: 10.1136/bmjopen-2019-031598
|View full text |Cite
|
Sign up to set email alerts
|

Impact of non-menthol flavours in e-cigarettes on perceptions and use: an updated systematic review

Abstract: ObjectivesGiven the exponential increase in the use of e-cigarettes among younger age groups and in the growth in research on e-cigarette flavours, we conducted a systematic review examining the impact of non-menthol flavoured e-cigarettes on e-cigarette perceptions and use among youth and adults.DesignPubMed, Embase, PyscINFO and CINAHL were systematically searched for studies published and indexed through March 2018.Eligibility criteriaQuantitative observational and experimental studies that assessed the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 78 publications
2
57
0
Order By: Relevance
“…A variety of intervention strategies may help to reduce the availability and appeal of e-cigarettes among youth. For example, given that the appealing flavours are an important reason for youth use of e-cigarettes (Meernik et al 2019), limiting the number and types of e-cigarette flavours available may help to reduce their appeal and use among youth. Data from clinical trials suggest that lowering the nicotine content of cigarettes reduces cigarette consumption among adults (Benowitz et al 2012;Donny et al 2015); it is possible that a similar approach to limiting the amount of nicotine that is permitted in pods and e-liquid may help to reduce e-cigarette use among youth.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of intervention strategies may help to reduce the availability and appeal of e-cigarettes among youth. For example, given that the appealing flavours are an important reason for youth use of e-cigarettes (Meernik et al 2019), limiting the number and types of e-cigarette flavours available may help to reduce their appeal and use among youth. Data from clinical trials suggest that lowering the nicotine content of cigarettes reduces cigarette consumption among adults (Benowitz et al 2012;Donny et al 2015); it is possible that a similar approach to limiting the amount of nicotine that is permitted in pods and e-liquid may help to reduce e-cigarette use among youth.…”
Section: Discussionmentioning
confidence: 99%
“…Food and Drug Administration, 2019). The wide variety of flavors available in e-cigarettes (which are no longer available in cigarettes) may be particularly appealing to youth, and are cited as a primary reason for use among youth in many studies (Huang et al, 2017, Meernik et al, 2019). In fact, one study showed that 78% of youth reported that they would not use an e-cigarette if it were not flavored.…”
Section: Introductionmentioning
confidence: 99%
“…Study participants also cited flavors as a reason for tobacco product experimentation and use. Meernik et al subsequently produced an updated review that looked specifically at nonmenthol-flavored ENDS and found that flavors increased product appeal and willingness to try and use ENDS and decreased harm perceptions of ENDS use among youth [ 20 ]. They also found among adults that flavors increased product appeal and were cited as a reason for ENDS use but that the effects of flavors on smoking cessation were not clear.…”
Section: Discussionmentioning
confidence: 99%